2021
DOI: 10.7150/jca.58640
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs as novel potential biomarkers for pancreatic cancer

Abstract: Pancreatic cancer (PaCa) is the fourth leading cause of cancer-related deaths in the United States, and the vast majority of these malignancies are pancreatic ductal adenocarcinomas (PDAC), but there is still a lack of early detection biomarkers for PaCa. Unlike linear RNAs, circRNAs form covalently closed continuous loops and can act as mammalian gene regulators. They may be diagnostic or predictive biomarkers for some tumors, also be novel potential therapeutic targets in different diseases. This review focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 112 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…Emerging evidence shows that circRNAs possess closely associated with the pathogenesis and progress of various cancers. Previous studies have demonstrated that a number of circRNAs were aberrantly expressed in PC ( 22 24 ). Nevertheless, the role and mechanism of circRNAs in regulating immune microenvironment of PC remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence shows that circRNAs possess closely associated with the pathogenesis and progress of various cancers. Previous studies have demonstrated that a number of circRNAs were aberrantly expressed in PC ( 22 24 ). Nevertheless, the role and mechanism of circRNAs in regulating immune microenvironment of PC remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Noncoding RNAs (ncRNAs), which include small nuclear RNAs (snRNAs), small nucleolar RNAs (snoRNAs), microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs), are RNA molecules that arise from genomic regions without protein-coding potential and display a variety of mechanisms and functions by regulating gene expression at the transcriptional, RNA processing, and translational levels and participating in virtually all cellular processes [ 1 , 2 ]. Dysregulated ncRNAs are involved in many complex human diseases and exert distinct functions, such as oncogenic and tumor-suppressive roles [ 1 , 3 , 4 , 5 ]. In this Special Issue, we gathered six articles—three original research contributions, one communication, and two review articles—that focused on the latest findings and important perspectives of the molecular mechanisms and clinical implications of ncRNAs in various cancers, including the discovery and structural prediction of novel miRNAs, as well as the mechanism of miRNAs and lncRNAs in cancer proliferation, metastasis, invasion, and drug resistance and their clinical application as potential new biomarkers and therapeutic drugs.…”
mentioning
confidence: 99%